A comprehensive clinical and laboratory evaluation of 224 patients with persistent symptoms attributed to presumed tick-bite exposure. - Kenneth Nilsson; Elisabet Skoog; Viktor Jones; Lisa Labbé Sandelin; Christina Björling; Ester Fridenström; Marie Edvinsson; Andreas Mårtensson; Björn Olsen (PLoS ONE)
Background Persistent symptoms attributed to presumed tick-bite exposure constitute an unresolved medical controversy. We evaluated whether Swedish adults who met the criteria for post-treatment Lyme disease syndrome (PTLDS) exhibited characteristics distinguishable from adults who did not, but who displayed similar symptoms and disease course after suspected previous tick-bite infection (TBI). Methods and findings During 2015-2018, 255 patients-referred to the Centre for Vector-borne Infections, Uppsala University Hospital, Sweden with symptoms lasting longer than six months-were recruited. Of this group, 224 completed the study. Each patient was examined by an infectious disease specialist and, besides a full medical history, underwent a panel of blood and cerebrospinal fluid laboratory tests including hematological, biochemical, microbiological and immunological analyses, and the RAND-36 scale to measure quality of life. For analysis purposes, patients were divided into five subgroups, of which one represented PTLDS. According to serological results indicating TBI and documented/ reported objective signs of Lyme disease, 85 (38%) patients fulfilled the criteria for PTLDS and were compared with the other 139 (62%) serologically classified patients. In the PTLDS group, erythema chronicum migrans (ECM) was documented/reported in 86% of patients, previous neuroborreliosis in 15%, and acrodermatitis chronica atroficans (ACA) in 3.5%. However, there were no significant differences regarding symptoms, laboratory results or disease course between patients with PTLDS and those without laboratory evidence of Borrelia exposition. Most reported symptoms were fatigue-related (70%), musculoskeletal (79%), neurological (82%) and neurocognitive (57%). Tick bites were recalled by 74%. The RAND-36 score was significantly below that of the general Swedish population. Signs of immunological/inflammatory reactivity with myositis antibodies were detected in 20% of patients, fibrinogen levels were moderately increased in 21% and elevated rheumatoid factor in 6%. Conclusions The PTLDS group did not differ exclusively in any respect from the other subgroups, which either lacked previously documented/reported evidence of borreliosis or even lacked detectable serological signs of exposure to Lyme disease. The results suggest that symptoms often categorized as Chronic-Lyme-Disease (CLD) in the general debate, cannot be uniquely linked to Lyme disease. However, approximately 20% of the total group of patients showed signs of autoimmunity. Further studies are needed to elucidate the underlying causes and mechanisms of PTLDS and there is reason to consider a multifactorial approach.